Experimental encryption multiplexing based on a JTC scheme - Tebaldi, Myrian Cristina; Vargas, Carlos; Bolognini, Nestor; Torroba, Roberto (Photonics Letters of Poland, 2010)
We present an alternative scheme to perform a multiple encrypting technique based on the use of a Joint Transform Correlator architecture. The basic approach relies on using an extra random phase mask placed before the correlator input plane, where we select different disjoint regions to encode each input object. In this way we avoid the cross talking when reconstructing the encoded objects. We experimentally validated the procedure using a photorefractive crystal as a storing medium. Full text: PDF References: P. Refregier, B. Javidi,"Optical image encryption based on input plane and Fourier plane random encoding", Opt. Lett. 20, 767 (1995). [CrossRef] E. Tajahuerce, O. Matoba, S. C. Verrall, B. Javidi,"Optoelectronic information encryption with phase-shifting interferometry", Appl. Opt. 39, 2313 (2000). [CrossRef] G. Unnikrishnan, J. Joseph, K. Singh, "Optical Encryption System That Uses Phase Conjugation in a Photorefractive Crystal", Appl. Opt. 37, 8181 (1998). [CrossRef] J. F. Barrera, R. Henao, M. Tebaldi, N. Bolognini, R. Torroba, "Multiplexing encryption-decryption via lateral shifting of a random phase mask", Opt. Commun. 259, 532 (2006). [CrossRef] J. F. Barrera, R. Henao, M. Tebaldi, N. Bolognini, R. Torroba, "Multiplexing encrypted data by using polarized light", Opt. Commun. 260, 109 (2006). [CrossRef] G. Unnikrishnan, J. Joseph, K. Singh, "Optical encryption by double-random phase encoding in the fractional Fourier domain", Opt. Lett. 25, 887 (2000). [CrossRef] E. Tajahuerce, B. Javidi, "Encrypting three-dimensional information with digital holography", Appl. Opt. 39, 6595 (2000). [CrossRef] X. Peng, P. Zhang, H. Wei, B. Yu, "Known-plaintext attack on optical encryption based on double random phase keys", Opt. Lett. 31 1044 (2006). [CrossRef] Y. Frauel, A. Castro, T. J. Naughton, B. Javidi, "Resistance of the double random phase encryption against various attacks", Opt. Exp. 15, 10253 (2007). [CrossRef] T. Nomura, B. Javidi, "Optical encryption using a joint transform correlator architecture", Opt. Eng. 39, 2031 (2000). [CrossRef] D. Amaya, M. Tebaldi, R. Torroba, N. Bolognini, "Digital color encryption using a multi-wavelength approach and a joint transform correlator", J. Opt. A: Pure Appl. Opt. 10, 104031 (2008). [CrossRef]